2002
DOI: 10.1126/science.1067123
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Storage in Groundwater Systems

Abstract: The dynamic nature of groundwater is not readily apparent, except where discharge is focused at springs or where recharge enters sinkholes. Yet groundwater flow and storage are continually changing in response to human and climatic stresses. Wise development of groundwater resources requires a more complete understanding of these changes in flow and storage and of their effects on the terrestrial environment and on numerous surface-water features and their biota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
377
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(380 citation statements)
references
References 59 publications
2
377
0
1
Order By: Relevance
“…W ðtÞ ¼f ðtÞ½c 0 þ c 1 ðt − t 0 Þ : [11] This reflects both the recent redistribution of land use in the logistic curve and the long-term linear trend of increasing crop water use efficiencies (70). The coefficients inf were constrained to match existing redistribution trends of the median line in Fig.…”
Section: Appendix B Agricultural Production Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…W ðtÞ ¼f ðtÞ½c 0 þ c 1 ðt − t 0 Þ : [11] This reflects both the recent redistribution of land use in the logistic curve and the long-term linear trend of increasing crop water use efficiencies (70). The coefficients inf were constrained to match existing redistribution trends of the median line in Fig.…”
Section: Appendix B Agricultural Production Methodsmentioning
confidence: 99%
“…The wise management of groundwater resources requires a more comprehensive understanding of the relationships between aquifer pumping and the capacity of the terrestrial environment to provide ecosystem goods and services upon which society depends (6,11). Informed decision making of processes involving the controls and feedbacks between society and ecosystems is founded on increased understanding of the relevant interdisciplinary linkages (3,12).…”
mentioning
confidence: 99%
“…Much of this understanding was achieved by using modeling approaches that consider the hydrology and soil chemistry separately, that assume simplified steady-state flow for spatial scales not larger than the field, and that only consider the RZ. However, recent research (6)(7)(8)(9)(10)(11) has shown that soils must be fully coupled with the vadose zone and groundwater systems for regional-scale studies, especially in areas where groundwater tables are shallow or groundwater pumping is used (12). Innovative predictive tools are needed that can be applied at the regional scale and at the long term, so that the sustainability of alternative management strategies can be evaluated.…”
mentioning
confidence: 99%
“…An extended evaluation of largescale groundwater models may be feasible with GRACE data. These models will also support the analysis of aquifer responses to water withdrawals in terms of reduced discharge or reduced storage (Alley et al 2002). At continental and global scales, the observed storage variations are an important contribution to the understanding of the global water cycle and its response to climate variability.…”
Section: Perspectives For Hydrogeologymentioning
confidence: 99%